Boswell's enlightenment - Zaretsky, Robert 1955- (<<The>> Belknap Press of Harvard Univ. Press, 2015)
Prologue : the view from Arthur's Seat -- In the Kirk's shadow -- At home with Hume -- A journal is born -- Enter Johnson -- Derelict in Utrecht -- Belle de Zuylen -- Aufklarüng Agonistes -- The distance between Môtiers and Ferney -- On libertines and liberty -- After Corsica, before futurity